PROJECT MODELLING TOOLBOX IN HIGHER EDUCATION: HEXAGONAL CANVAS IN PROJECT BASED LEARNING - Sokolovs, Alvis; Grinfelde, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Inclusion of project modelling tools into higher education is based on expectations of industry about young professionals with applicable, rich skillset. Business or project model canvas is one of the most widely used frameworks in contrary to traditional planning tools. Pedagogically - project model canvas is a teaching goal and method simultaneously. Those aspects widen possibilities to integrate the tool in various study courses and levels. The aim of the research is to explore and evaluate functional and cognitive impacts of Hex-canvas use in project-based learning in higher education. This tool is represented in a form of template of 11 fundamental elements which describe a specific aspect of a project. The research is based on experiences gathered in Vidzeme University of Applied Sciences, Latvia. Data used in this research has been comprised of structured interviews of doctoral level students (n=8) who used Hex-canvas in summer school and from bachelor and master level students (n=16) of “I Living Labs” study course (year 2022). Results reveal high applicability in structuring of the projects, defining aims and activities for implementation, it gives overall perspective of project, however there must be clear instructions by teachers, as well the consistency of usage is recommended.